DESTINATION BRANDING STRATEGY BENDOSARI TOURISM VILLAGE-MALANG REGENCY, THROUGH CREATING A VISUAL IDENTITY - Putri, Safitri Aprillia; Cahyaning Umul Chasanah Nursyifani; Rizky Ageng Syaputra; Priska Arindya Purnama; Dian Pratiwi Willyarti (SEEIJ (Social Economics and Ecology International Journal), 2025)
Bendosari Tourism Village, Malang Regency is one of the strategic alternative tourist destinations because Bendosari borders directly with Batu City, Blitar Regency and Kediri Regency. Bendosari Tourism Village has diverse potentials, including natural tourism, village products such as agriculture, plantations, and technological innovations such as biogas. In addition, what makes this village interesting is that it still maintains customs, local wisdom and community culture. To maximize this potential, a strong and representative visual identity is needed. The purpose of this design is to produce a visual identity that can represent the image of Bendosari Tourism Village which can be implemented in various media according to the needs to create the identity of Bendosari tourism village. The method used in this study is a qualitative method consisting of observation, interviews, documentation, and literature studies. The results of this design are an attractive and easily recognizable Bendosari Tourism Village logo that reflects the diversity of village potential and its application design in various promotional media and merchandise, such as brochures, banners, social media promotions, t-shirts, hats, and others. The implementation of this visual identity aims to increase the visibility of Bendosari Tourism Village, attract visitors, and promote local products and innovations. This research is expected that visual identity can support destination branding strategy and contribute to tourism development and village community empowerment. With the design of visual identity and promotional media for Bendosari Tourism Village, it can help improve image, expand market segmentation and provide its own characteristics for Bendosari Tourism Village so that it can compete in the world of tourism.